(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To assess how enterostomal therapy nurses perceive entrepreneurship within the specialty. Method: A qualitative, descriptive, and exploratory study conducted through semi-structured interviews between January and April 2020, involving 26 entrepreneurial enterostomal therapy nurses recruited using the “Snowball” sampling technique. The collected data were transcribed and subjected to thematic content analysis. Results: The findings revealed a range of perceptions from nurses regarding entrepreneurship in enterostomal therapy, leading to the discussion of the following themes: entrepreneurship in nursing and enterostomal therapy; the enterostomal therapist’s view of the entrepreneurial process; and the traits of the entrepreneurial enterostomal therapist. Enterostomal therapy nurses perceive nursing-related entrepreneurship as a proactive, innovative approach, with a growth-oriented perspective within the specialty. They perceive entrepreneurial practice as essential for creating new professional opportunities. Conclusion: Entrepreneurship is viewed as an appealing means to enhance autonomy and improve professional performance. It emphasizes the crucial role of developing entrepreneurial skills to excel in various professional environments.